Review of social media intervention in adult population during COVID-19 pandemic based on Protection Motivation Theory - Muhammad Prima Cakra Randana; Rizma Adlia Syakurah (Intelektual Pustaka Media Utama, 2021)
During COVID-19 pandemic, social media has become a basis for information deployment, it has the potential to change people opinion and solve many issues in this situation. Based on Protection Motivation Theory (PMT), threat and coping appraisal were predictors to behavioral responses in pandemics. This study aimed to analyze the impact of social media intervention in adult population during COVID-19 pandemic based on PMT. This review was created using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) and data collection from electronic databases such as Pubmed, Mendeley app, Europe PMC, Cochrane Databases, Science Direct, and Wiley Online Library. Inclusion criteria consists of English studies, studies related to the topic and match with required variables. There are five cross-sectional studies involving a total of 2.448 participants that were published in 2020. Among all categories based on included studied, it was shown that cyberchondria, perceived severity and perceived vulnerability are predictors in social media, related to behavioral responses during COVID-19 pandemic. Reducing information overload, related to cyberchondria, via the clear structuring and communication of reliable health information is needed. Hence, educating people on responsible and healthy social media use could help alleviate the observed negative consequences from perceived severity and vulnerability.